A Comparative Study to Assess the Efficacy of Two Different Estradiol Formulations during In Vitro Fertilization. (10th August 2021) - Banker, Manish; Arora, Parul; Banker, Jwal; Shah, Sandeep
Abstract : Improvements in stimulation protocols, introduction of vitrification, and changes in clinical practices have contributed to improved efficacy and safety of assisted reproductive technology (ART) procedures. This has also led to a concomitant increase in number of cycles requiring hormone replacement therapy (HRT) protocol for performing an embryo transfer. Successful implantation is dependent on endometrial thickness which in turn is regulated by temporal regulation of hormones. Careful control of estrogen levels determines uterine receptivity. One of the most used drugs for achieving appropriate endometrial lining of >7 mm in HRT is estradiol valerate. Although different estrogen formulations with varying physicochemical properties exist, there is not enough literature to support if the differences translate into a discernible clinical outcome in an in vitro fertilization (IVF) setting. Objective and Method . In this study, retrospective in nature, we compare the efficacy of oral estradiol hemihydrate with estradiol valerate in HRT cycles in 2, 529 Indian women, undergoing treatment at a center in India between Jan 2017 and May 2019. Results . Our results primarily indicate that between the estradiol valerate and estradiol hemihydrate treatment groups, the implantation rate (IR) was 47.42% and 49.07%, respectively (P value 0.284), and the endometrial thickness (mean ± SEM in mm) that was achieved was 9.25 ± 0.038  mm and 9.57 ± 0.058  mm (P value < 0.001), respectively. There were no significant differences observed in the secondary outcome measures including clinical pregnancy rate, abortion rate, ectopic pregnancy, and live birth rate. Conclusions . Hence, this study concludes that oral estradiol hemihydrate and estradiol valerate are therapeutically equivalent and provide similar clinical outcomes in an IVF setting.